The Toxic Effects of Cyclosporine on Splenic Tissue of Rat and it’s Amelioration with Nigella Sativa - Younus, Nadia; Sultana, Kishwar; Ali, Asma Basharat (International Journal of Pathology, 2018)
Background: Cyclosporine is an immunosuppressive drug. Its mechanism of action is inhibition of T cells activation. Cyclosporine has toxic effects on many organs including spleen. Nigella sativa is an immunomodulatory agent. It increases lymphocyte population and also has promising anti-oxidative effects. Objective: Observe the toxicity of cyclosporine and evaluate the ameliorative effects of Nigella Sativa in spleenMaterial and Methods: This study was conducted in Baqai Medical University from November 2016 to December 2016. Sprague Dawley rats were randomly divided into three groups. Group A was control, group B was given oral cyclosporine only and group C was given cyclosporine with Nigella sativa. At the end of study period animals were sacrificed and spleen was harvested.Results: Body weight of cyclosporine group B was decreased significantly (P<0.001) in comparison to control A and increased in Nigella sativa and cyclosporine group C. Absolute and relative spleen weights were also decreased in cyclosporine group B and increased in Nigella sativa and cyclosporine group C. Morphometric examination of splenic tissue showed thickened capsule, congested red pulp, reduced white pulp and hyalinosis and vacuolization in central artery in cyclosporine group B while these features were reduced in Nigella sativa and cyclosporine group C.Conclusion: Cyclosporine caused toxicity in spleen while Nigella sativa was helpful in ameliorated these effects.